Marangoni boundary layer flow over a permeable surface in the presence of thermal radiation - Mohd Ariffin, Norfarahanim (2017)
Marangoni convection is a flow induced by the surface tension gradients associated with either thermal or concentration gradients. In this study, the problem of Marangoni boundary layer is derived in three different types of fluid over a permeable surface, where there is suction or injection effect. The scope of this thesis is restricted to two dimensional, steady, incompressible and laminar flow considered in micropolar fluid, nanofluid and viscous fluid. Each problem is considered in different type of fluid with respect to the parameters interest. The effect of thermal radiation is considered due to its vast applications and large contribution in the field of science and technology and it is occurring in the heat equations. The consumption of suction or injection effect is also utilized to determine the effect of it on the flow and heat transfer characteristics. The governing nonlinear partial differential equations are transformed into a system of nonlinear ordinary differential equations using similarity transformation. Then the resulting systems of equations are solved numerically. Numerical results are presented in tables and graphs for the velocity, temperature and concentration profiles are analysed with respect to the involved parameter interest namely types of concentration (weak and strong), radiation, magnetic field and suction or injection parameter. Comparisons with known results from the previous literature have been made in order to ratify the numerical results obtained in this thesis and the injunction showing very good agreements. All the governing parameters affect the flow and heat transfer characteristics of the fluid except for the radiation parameter. It only affects the heat transfer rate of the fluid as it decreases the flow rate. While the suction gave a decrement to the heat transfer and injection proposed an opposite results.